Do nano-boom à paralisação: a trajetória da política brasileira de nanotecnologia - Noela Invernizzi; Guillermo Foladori; Josemari Perschke de Quevedo (Ciências Sociais Unisinos)
Brazil formulated a policy to spur the emergent field of nanotechnology at the beginning of 2000 decade, in synchrony with industrialized countries. The area was declared strategic in the country´s science, technology and innovation policy since 2004, and considered a motor to increase competitiveness. In this article we assess the trajectory of nanotechnology policy throughout 15 years, since the initial euphoria to current virtual shutdown due to funding cuts. We analyze how the policy agenda was constructed, highlighting international influences and the prominent role played by nanotechnology scientists. Then, we examine four dimensions of the formulation and implementation of the policy: scientific capacity building, promotion of innovation, issues of risks and regulation, and social implications matters. We claim that the policy was conceived within a narrow governance approach, which was broadened over time as a result of pressures coming from the local and international contexts. Finally, we problematize the mismatch between the strategic status given to nanotechnology and the lack of real prioritization revealed by funding instability. Information sources are mainly documentary, complemented by direct observation of relevant meetings and interviews with policy makers.